Hubungan Komunikasi dengan Kepuasan Pernikahan pada Ibu Rumah Tangga Penggemar Tayangan Drama Korea - Novaria Maulina; Atika Atika (ULTIMA Comm, 2020)
Marriage communication is one of the keys to maintain relationships between spouses. Communication behaviors that reveal negative feelings to partners such as criticism, self-defense, humiliation and withdrawal can be the beginning of dissatisfaction and divorce. On the other hand, positive feelings expression has its own effect on the stability of the marriage relationship over time. The purpose of the study was to measure the correlation of communication with the marriage satisfaction of housewives who were Korean drama fans. The study used a quantitative approach with an explanatory type. The population in this study was housewives who were Korean drama fans. Data collection through questionnaires and the Spearman's rank correlation test was used to measure the correlation between the two variables in this study (Marriage Communication and Marriage Satisfaction). Based on the study results, there is a strong and significant correlation between Marriage Communication and Marriage Satisfaction. The strength of the correlation is proven with the correlation value of 0.692 and the significance level at 0,000. It shows that when the partner's marriage communication is getting better or positive, then the couple has satisfaction in their marriage. Keywords: marriage communication, marriage satisfaction, Korean drama